Social topics on social media: a communicative approach - Mohamed BOUKHOBZA (Eon)
Social media has revolutionized discussions on social issues by facilitating real-time engagement and amplifying marginalized voices. It fosters community building, raises awareness through visual storytelling, and serves as a mobilizing tool for activism. However, the rapid proliferation of misinformation underscores the importance of developing critical media literacy. This essay examines the transformative impact of social media in shaping conversations around social issues, focusing on both its benefits and challenges. It analyzes their influence on raising awareness, activism, community building, and ethical issues related to privacy, representation, and misinformation. The study shows that social media plays a key role in community engagement, socio-political education, and mobilization. It offers a platform for marginalized voices, facilitates international discussions, and improves mental ell-being through social connections. However, the spread of misinformation and ethical challenges related to privacy and representation remain major obstacles to overcome.